Expression of the membrane protein tyrosine phosphatase CD148 in human tissues - Autschbach, Frank; Mechtersheimer, Gunhild; Rohr, Claudia; Gaßler, Nikolaus; Otto, Herwart F.; Schraven, Burkhart (Tissue antigens, 1999)
CD148, a receptor-like protein tyrosine phosphatase also known as HPTP-eta/DEP-1, is involved in signal transduction in leucocytes and is thought to contribute to mechanisms of cellular differentiation. We have investigated the in situ expression of CD148 in various fresh-frozen tissues by immunohistology and analyzed its expression on subpopulations of activated peripheral blood leucocytes by flow cytometry. In lymphoid organs, CD148 was found to be widely expressed on B and T cells, granulocytes, macrophages, certain dendritic cells as well as mature thymocytes. The cellular level of CD148 was increased after in vitro activation of peripheral blood leucocytes. Comparative analysis of tissue samples from normal gut and from patients with active Crohn's disease showed that leucocytes expressing CD148 are significantly upregulated in inflamed tissues and that a subset of these cells co-express the activation marker CD25. In non-lymphoid tissues, CD148 was found to be present on many epithelial cell types with glandular and/or endocrine differentiation as well as on fibrocytes, melanocytes and Schwann cells. CD148 expression was maintained also in malignant counterparts of such tissues. However, a marked loss of CD148 immunoreactivity was apparent in some of the investigated high-grade carcinomas. In summary, our results confirm a role of CD148 as a leucocyte activation marker. Among non-hematopoietic cells, CD148 is expressed by characteristic types of epithelial and non-epithelial cells. Downregulation of CD148 might promote dedifferentiation and autonomous growth of such cells in malignant tumors.
Gesehen am 02.11.2017